Asuhan Kebidanan Continuity of Care pada Ny. M Umur 25 Tahun di Balikpapan - Sodiyah; Risma Aliviani Putri (Universitas Ngudi Waluyo, 2024)
The Maternal Mortality Rate and Infant Mortality Rate are one of the indicators of health development in the National Medium Term Development Plan. One effort to reduce MMR and IMR is to provide continuous midwifery care starting from pregnancy, delivery, postpartum. The aim of the research is to provide midwifery care to Mrs. M comprehensively from pregnancy, childbirth, postpartum, newborn and family planning care. The research method used is analytical descriptive observational. The sample was pregnant women in the second trimester, 26 weeks of gestation, G1P0A0, 25 years old. Research time 25 May to 24 August 2024 at RSIA Asih Balikpapan. The research instrument uses the SOAP documentation method and the KIA book. Collection techniques use primary data through interviews, observations, physical examinations, KIA books. During pregnancy care in the second and third trimesters, the mother complained of frequent urination, was given IEC regarding the discomfort of the second and third trimesters of pregnancy, recommended personal hygiene. In the first stage of labor, the mother experienced PROM and was advised to take bed rest. The care provided is to help reduce pain and anxiety during childbirth while reducing medical intervention by providing complementary counter pressure massage therapy. Then a CTG examination was carried out with Fetal Low Variability results, Sectio Ceserea Cito surgery doctor's advice with an indication of 6 hour PROM and Fetal Low Variability, there was a gap in delivery care. During the care of newborns and postpartum babies, no defects or danger signs were found, everything went normally. The mother had used post-placental contraception, then was given IEC after IUD installation. Conclusion From the management, comprehensive care has been provided to the mother through pregnancy, childbirth and postpartum which were physiological without complications Abstrak Angka Kematian Ibu dan Angka Kematian Bayi menjadi salah satu indicator dari pembangunan kesehatan dalam Rencana Pembangunan Jangka Menengah Nasional. Salah satu upaya untuk menekan AKI dan AKB itu adalah memberikan asuhan kebidanan yang berkesinambungan mulai dari hamil, bersalin, nifas. Tujuan penelitian memberikan Asuhan Kebidanan Pada Ny. M secara komprehensif dari asuhan kehamilan, persalinan, nifas, bayi baru lahir dan KB. Metode penelitian yang digunakan adalah observasional deskriptif analitik. Sampel adalah ibu hamil trimester II usia kehamilan 26 minggu, G1P0A0 umur 25 tahun. Waktu penelitian 25 Mei sampai 24 Agustus 2024 di RSIA Asih Balikpapan. Instrument penelitian menggunakan metode dokumentasi SOAP dan buku KIA. Teknik pengumpulan menggunakan data primer melalui wawancara, observasi, pemeriksaan fisik, buku KIA. Pada Asuhan kehamilan di trimester II dan III ibu mengeluh sering BAK, diberikan KIE mengenai ketidaknyamanan kehamilan trimester II dan III, menganjurkan personal hygiene. Pada persalinan Kala I ibu mengalami KPD dan menganjurkan untuk bedrest. Asuhan yang di berikan untuk membantu mengurangi nyeri dan kecemasan dalam persalinan sekaligus mengurangi intervensi medis dengan memberikan terapi komplementer massage’’Counter Pressure’’. Kemudian dilakukan pemeriksaan CTG dengan hasil Fetal Low Variability, Advis dokter operasi Sectio Ceserea Cito dengan indikasi KPD 6 jam dan Fetal Low Variability, dalam asuhan persalinan terdapat kesenjangan. Pada asuhan bayi baru lahir dan nifas tidak ditemukan adanya cacat serta tanda bahaya, semua berjalan normal. Ibu sudah menggunakan kontrasepsi post plasenta, kemudian di berikan KIE post pemasanga IUD. Kesimpulan Dari penatalaksanaan telah dilakukan asuhan komprehensif pada ibu dari kehamilan, persalinan, dan nifas yang fisiologis tanpa penyulit.